2009
DOI: 10.1177/0009922809337534
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Completion of the Human Papillomavirus Vaccine Series

Abstract: Charts were reviewed until November 26, 2008, for a minimum 17 months of follow-up. Completion was defined as receipt of 3 HPV vaccinations. Charts were reviewed for age, race/ethnicity, type of insurance (private vs Medicaid/Child Health Insurance Program [CHIP]), and distance from home to the clinic. Sexual history variables included sexual activity status prior to initiation of the series and history within 3 years of vaccine initiation of a gynecological exam and/or Papanicolaou (Pap) test, HPV DNA test, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
53
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 11 publications
11
53
0
Order By: Relevance
“…These findings are consistent with other studies; Neubrand et al (2009) showed that Hispanics were 60% less likely than whites to complete vaccination. Widdice and colleagues ( 2011) showed that blacks and publicly insured patients were 50% and 24% less likely than whites and privately insured patients, respectively, to complete vaccination.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with other studies; Neubrand et al (2009) showed that Hispanics were 60% less likely than whites to complete vaccination. Widdice and colleagues ( 2011) showed that blacks and publicly insured patients were 50% and 24% less likely than whites and privately insured patients, respectively, to complete vaccination.…”
Section: Discussionsupporting
confidence: 93%
“…7 Female patients who self-identified as black, compared with those who selfidentified as white, were less likely to complete vaccination within 7 and 12 months. This is consistent with previous reports of HPV4 vaccine completion 8,20,36,37 as well as hepatitis B vaccine completion in adolescents. 25,30,38 This disparity is concerning given that the incidence of and mortality from cervical cancer is higher among black women than white women in our community and nationally.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the modeling of beneficial effects from herd immunity is only speculative until vaccine uptake increases. Regarding vaccine compliance, not everyone who initiates the vaccine series completes all 3 doses or completes all doses in the recommended 6-month time frame, 55 and it is presently unknown how noncompliance affects vaccine efficacy and duration of protection.…”
Section: ■■ Discussion and Limitationsmentioning
confidence: 99%